Multilayer electrostatic spinning artificial dura mater capable of being degraded and absorbed and preparation method of multilayer electrostatic spinning artificial dura mater

By using multi-layer structure electrospinned artificial dura, using materials such as polyptioxane and polyvinyl alcohol, the problems of insufficient inabsorbability, degradation speed and mechanical properties of the materials in the prior art are solved, and the good biocompatibility and degradation performance of the materials are achieved, ensuring the safety and effectiveness of dura repair.

CN119746153APending Publication Date: 2025-04-04TIANJIN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411961547.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing artificial dura materials used for meningeal injury repair have problems such as limited sources, immune rejection, high cost, non-absorbance, degradation speed and insufficient mechanical properties, resulting in limited clinical application.

Method used

The electrospinned artificial dura mater is adopted with a multi-layer structure composed of an inner layer film, a transition layer film and an outer layer film. The inner layer film is made of polydioxycyclohexanone, the transition layer film is made of mixed polydioxycyclohexanone and polyvinyl alcohol, and the outer layer film is made of polyvinyl alcohol, which is prepared by electrospinning technology to achieve a stable connection between the hydrophobic anti-adhesion layer and the hydrophilic cell scaffold layer.

Benefits of technology

It achieves good biohistocompatibility of the material, complete degradation and absorption, moderate degradation speed, no immune repulsion, and has mechanical strength, thickness and flexibility comparable to the human dura. The inner and outer layers are reliable in connection, which can effectively prevent brain adhesion and is easy to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746153A_ABST
    Figure CN119746153A_ABST
Patent Text Reader

Abstract

The invention discloses a multilayer electrostatic spinning artificial dura mater capable of being degraded and absorbed and a preparation method thereof. The artificial dura mater is formed by compounding an inner layer film, a transition layer film and an outer layer film which are sequentially arranged, the inner layer film is a hydrophobic anti-adhesion layer formed by electrostatic spinning of poly (p-dioxanone) with the viscosity-average molecular weight of 5.0 * 10 < 4 >-2.1 * 10 < 5 >; the transition layer film is a middle layer formed by electrostatic spinning of poly (p-dioxanone) with the viscosity-average molecular weight of 5.0 * 10 < 4 >-1.2 * 10 < 5 > and polyvinyl alcohol with the viscosity-average molecular weight of 1.45 * 10 < 5 >-2 * 10 < 5 > according to the weight ratio of 2: 8-8: 2; the outer layer membrane is a hydrophilic cytoskeleton layer formed by carrying out electrostatic spinning on polyvinyl alcohol of which the viscosity-average molecular weight is 1.45 * 10 < 5 >-2 * 10 < 5 >; the artificial dura mater has high similarity with the dura mater of a human body, has good biological tissue compatibility and complete degradability with moderate degradation speed, and is adaptive to the dura mater of the human body in mechanical strength, thickness and flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a multi-layered, degradable and absorbable electrostatic spinning artificial dura mater and a preparation method thereof. Background Art

[0002] The dura mater is a solid connective tissue membrane on the outermost layer of the brain and spinal cord membrane structure. It is mainly composed of fibroblasts and collagen fibers and is an important barrier to protect brain tissue. Trauma or cranial surgery can cause dura mater defects. If not repaired in time, it can cause complications such as wound non-healing, subcutaneous effusion, and intracranial infection. In severe cases, it can cause cerebrospinal fluid overflow and endanger life.

[0003] At present, the materials for repairing dura mater defects mainly include autologous fascia, allogeneic materials, xenogeneic materials and artificial synthetic materials. Autologous fascia has good biocompatibility and low immune response, but its source is limited and it is expensive; allogeneic and xenogeneic materials have high immune rejection, and residual antigens can cause inflammatory reactions; although artificial synthetic materials are cheap and widely available, they are partially non-absorbable, and long-term retention in the body can easily cause a variety of complications. In addition, existing synthetic degradable materials have defects in in vivo degradation rate and mechanical properties, which limits their clinical application. Most of the existing artificial dura maters used for meningeal injury repair are layered structures to simulate the physiological function of the meninges. They are generally composed of an inner layer of hydrophobic material and an outer layer of hydrophilic material. However, the difference in the properties of the two layers of materials leads to poor connection reliability, which is prone to peeling and threatens the life and health of patients.

[0004] The published patent CN 109260520 B discloses a multifunctional dura mater repair material based on bionic design and its preparation method. The repair material is composed of an inner layer of polylactic acid electrospun membrane, a middle layer of chitosan-polylactic acid electrospun membrane, and an outer layer of gelatin-SIS powder hydrogel. Although it has regenerative activity, antibacterial and degradable properties, and can prevent leakage and adhesion, it has many shortcomings, including: the membrane thickness is very different from the thickness of the human dura mater, which will increase the difficulty and risk of surgery; the membrane pore size is not conducive to precise control of cell behavior, and the polylactic acid is not tough enough, which increases the difficulty of surgical suturing, and the degradation period of the material is as long as 18-24 months, which is easy to cause inflammation.

[0005] The published patent CN 101507661 B discloses a nano artificial dura mater with multiple functional layers and its preparation method. Although the artificial dura mater can achieve dura mater regeneration, the outer layer of hydrophilic material is directly electrospun on the inner layer of hydrophobic material. Due to the different material properties, the outer layer and the inner layer are not firmly connected and are easy to peel off, threatening the life safety of patients undergoing meningeal repair surgery.

[0006] The published patent CN 107823713 B discloses a multi-layer fused electrospun artificial dura mater and a preparation method thereof. The multi-layer artificial dura mater comprises a hydrophobic polycaprolactone electrospun inner layer, a hydrophilic polyglycolic acid electrospun outer layer and a fusion layer. The fusion layer is prepared by electrospinning a mixture of hydrophobic material polycaprolactone and hydrophilic material polyglycolic acid in multiple layers. The connection between any two adjacent layers is strengthened by a cylindrical groove structure to improve the bonding force between the layers, thereby solving the problems of dislocation and stratification of the artificial dura mater. However, the disadvantage is that the degradation time of polycaprolactone in the human body is relatively long, about 2-4 years, and there is a risk of causing inflammation. Polyglycolic acid is easily degraded by moisture absorption in the air, is difficult to preserve, and has poor antibacterial properties.

[0007] The published patent CN 103480042 A discloses an artificial dura mater and its preparation method and use method, wherein the artificial dura mater is composed of an oriented polylactic acid / glycolic acid copolymer fiber membrane as the inner layer and a non-oriented polylactic acid / glycolic acid copolymer-chitosan fiber membrane as the outer layer. Although the artificial dura mater can achieve the purpose of dura mater regeneration and prevention of scars and adhesions, it has the following shortcomings: in clinical application, the outer and inner fiber layers need to be placed at the defect of the meninges respectively, and an adhesive needs to be applied between the two layers, which greatly increases the inconvenience in clinical use.

[0008] In summary, the artificial dura mater materials reported in the prior art have many problems in terms of source, immune rejection, degradation performance, mechanical properties, interlayer bonding, and convenience in clinical use. There is an urgent need for an artificial dura mater material with excellent performance, easy use, safety and reliability. Summary of the invention

[0009] The purpose of the present invention is to provide a multi-layered, degradable and absorbable electrospun artificial dura mater that solves the above-mentioned technical problems.

[0010] The object of the present invention is to provide a method for preparing the above-mentioned multi-layer degradable and absorbable electrospun artificial dura mater.

[0011] To this end, the technical solution of the present invention is as follows:

[0012] A multi-layered, degradable and absorbable electrospun artificial dura mater, which is formed by sequentially arranged inner layer membrane, transition layer membrane and outer layer membrane; wherein,

[0013] The inner layer film is made of a viscosity average molecular weight of 5.0×10 4 ~2.1×10 5 The hydrophobic anti-adhesion layer is formed by electrospinning polydioxanone, and the pore size of the membrane ranges from 0.2 μm to 2 μm, and more preferably 2 μm;

[0014] The transition layer film is composed of a viscosity average molecular weight of 5.0×104 ~2.1×10 5 The polydioxanone with a viscosity average molecular weight of 1.45×10 5 ~2×10 5 The weight ratio of polyvinyl alcohol is 2:8 to 8:2, and the intermediate layer is formed by electrospinning, and the membrane pore size ranges from 2 μm to 20 μm, more preferably from 3 μm to 15 μm;

[0015] The outer layer film is made of a viscosity average molecular weight of 1.45×10 5 ~2×10 5 The hydrophilic cell scaffold layer is formed by electrospinning polyvinyl alcohol, and its membrane pore size ranges from 20 μm to 40 μm, and more preferably from 20 μm to 38 μm.

[0016] The artificial dura mater of the present invention adopts a three-layer membrane structure consisting of an inner membrane, a transitional membrane and an outer membrane; wherein the inner membrane adopts a viscosity-average molecular weight of 5.0×10 4 ~2.1×10 5 The polydioxanone was prepared into a spinning solution with an appropriate mass fraction and prepared by electrospinning; the outer layer membrane was made of a polydioxanone with a viscosity-average molecular weight of 1.45×10 5 ~2×10 5 The polyvinyl alcohol is formulated into a spinning solution with an appropriate mass fraction and prepared by electrospinning; the middle transition layer is prepared by electrospinning a mixed spinning solution of the inner membrane material and the outer membrane material. According to the "like dissolves like" principle, the inner and outer layers are reliably combined to achieve enhanced bonding strength between the hydrophobic anti-adhesion layer and the hydrophilic cell scaffold layer, which is not easy to delaminate under the action of external force.

[0017] In terms of material selection, the inner layer membrane utilizes the excellent degradation performance and biocompatibility of polydioxanone, including the degradation products in the body being water and carbon dioxide, which are non-toxic and harmless to the human body and can be excreted from the body through normal physiological metabolic pathways. The degradation process is relatively simple and safe, and no harmful substances will remain in the body, thereby reducing the risk of complications such as inflammation. Compared with the commonly used inner membrane materials formed by polylactic acid, acidic substances may be produced during the degradation of polylactic acid, which may affect the pH value of the microenvironment of the surrounding tissues to a certain extent. In addition, polydioxanone also has good flexibility and mechanical properties, enabling it to adapt to the complex physiological movements of the brain, such as rotation and shaking of the head, and is not easily ruptured by external forces. Its mechanical performance indicators such as tensile strength and elastic modulus can meet the requirements as the inner layer material of the dura mater, while preventing brain adhesions, it provides necessary structural support for the dura mater.

[0018] The inner layer film has a molecular weight of 5.0×10 4 ~2.1×10 5The inner layer film prepared by polydioxanone has good mechanical properties. According to comparative experiments, when the viscosity-average molecular weight of polydioxanone is lower than 5.0×10 4 When the viscosity-average molecular weight of polydioxanone exceeds 2.1×10 5 When the spinning solution is prepared, its solubility is low, and a longer time or more intense stirring conditions are required to fully dissolve it. The formed spinning solution is not stable, and new bubbles are generated during the static degassing time or during the static degassing process, which affects the stability of the electrospinning process and the quality of the fiber membrane. In terms of degradation performance, the higher molecular weight leads to a slower degradation rate and may cause the material to remain in the body for a long time and cause complications.

[0019] In terms of material selection, the hydrophilicity of polyvinyl alcohol is utilized to make the surface of the membrane structure able to attract water molecules to form a hydration layer, providing a favorable microenvironment for cell attachment and growth, and facilitating cell affinity, so that fibroblasts can more easily migrate, adhere, proliferate, grow and differentiate on this hydrophilic surface, thereby promoting the repair of meningeal tissue; compared with other commonly used hydrophilic materials, the hydrophilicity of polyvinyl alcohol also has the problem of structural instability due to excessive water absorption; in addition, polyvinyl alcohol also has good biocompatibility, so that it will not cause obvious immune rejection reactions in the body, coexist peacefully with surrounding tissues, and will not cause adverse effects on brain tissue, etc., ensuring safety during the dura mater repair process.

[0020] The outer layer film has a viscosity average molecular weight of 1.45×10 5 ~2×10 5 The polyvinyl alcohol also has the consideration of bioaffinity and mechanical properties; when the viscosity-average molecular weight of polyvinyl alcohol is lower than 1.45×10 5 When the outer membrane is inverted, the hydrophilicity and the ability to form a hydration layer will inevitably decrease, which will have a certain impact on the cell attachment and growth microenvironment, which is not conducive to the migration, adhesion, proliferation and growth differentiation of cells, and thus affect the repair effect of meningeal tissue; According to comparative experiments, the mechanical properties of the fiber membrane formed by polyvinyl alcohol with a lower molecular weight may be weakened, such as reduced strength and toughness, which may affect the stability of the entire artificial dura mater after combining with other layers, and it is more likely to be damaged when subjected to external forces; When the viscosity-average molecular weight of polyvinyl alcohol is higher than 2×10 5When electrospinning, the problem of low solubility also exists. Higher temperature and longer stirring time are required during the dissolution process, and the viscosity of the solution may increase significantly, which makes it easy to have difficulties in transporting the spinning solution during electrospinning, affecting the continuity of spinning and the uniformity of the fiber, and ultimately affecting the quality and performance of the artificial dura mater. In addition, higher molecular weight polyvinyl alcohol is not conducive to the pore size adjustment of the outer membrane, and it is impossible to achieve the appropriate pore size, i.e., 20μm to 40μm, which in turn affects the activity of fibroblasts on its surface and the tissue repair function.

[0021] Preferably, the thickness of the dura mater is 0.16 mm to 0.22 mm; the thickness of the inner membrane is 80 μm±10 μm, the thickness of the transitional membrane is 80 μm±10 μm, and the thickness of the outer membrane is 30 μm±10 μm.

[0022] Preferably, the diameter of the electrospun fibers of the inner layer membrane is 0.05 μm to 1 μm, more preferably 0.05 μm to 0.8 μm; the diameter of the electrospun fibers of the outer layer membrane is 0.5 μm to 3 μm, more preferably 0.5 μm to 2.2 μm; the diameter of the electrospun fibers of the transition layer membrane is 0.2 μm to 3 μm, more preferably 0.3 μm to 2.07 μm.

[0023] A method for preparing a multi-layered, degradable and absorbable electrospun artificial dura mater, comprising the following steps:

[0024] (1) electrospinning an inner layer membrane spinning solution having a solid content of polydioxanone of 14 wt% to 28 wt% to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are: a pump propulsion rate of 0.1 mL / h to 0.5 mL / h, a voltage of 12 kv to 20 kv, a receiving distance of 10 cm to 15 cm, and a spinning time of 3 h to 5 h;

[0025] (2) Based on the inner layer membrane, electrospinning is performed in the same direction on an inner layer membrane spinning solution with a solid content of 14wt% to 28wt% and an outer layer membrane spinning solution with a solid content of 6wt% to 12wt%, and the flow rates of the two spinning solutions are controlled so that the two are spun at a specified weight ratio to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are: pump propulsion rate 0.2mL / h to 0.7mL / h, voltage 12kv to 20kv, receiving distance 10cm to 15cm, spinning time 3h to 5h;

[0026] (3) On the basis of the transition layer membrane, an outer layer membrane spinning solution with a solid content of polyvinyl alcohol of 6wt% to 12wt% is electrospun to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are: pump propulsion rate 0.3mL / h to 0.9mL / h, voltage 10kv to 18kv, receiving distance 15cm to 20cm, and spinning time 3h to 5h.

[0027] Preferably, in step (1), the inner layer membrane spinning solution is prepared by dissolving polydioxanone in hexafluoroisopropanol, stirring for 4 h to 7 h to fully dissolve the polydioxanone, and preparing the inner layer membrane spinning solution.

[0028] Preferably, in step (2), the outer membrane spinning solution is prepared by dissolving polyvinyl alcohol in deionized water, stirring at 90°C to 100°C for 4h to 6h, and cooling to room temperature to prepare the outer membrane spinning solution.

[0029] Preferably, in steps (1) to (3), after the preparation of each spinning solution is completed, it is allowed to stand and degas for 1.5 hours to 3.5 hours.

[0030] Preferably, the multi-layer biodegradable and absorbable electrospun artificial dura mater further comprises step (4): the multi-layer electrospun membrane prepared through steps (1) to (3) is first rinsed with distilled water for 3 to 5 times, then dried at 40°C to 55°C for 2h to 4h, and then sterilized and vacuum-sealed and stored in a low temperature environment of -10°C to -30°C.

[0031] Compared with the prior art, the multi-layer degradable and absorbable electrospun artificial dura mater uses polydioxanone with good degradability and biocompatibility as a material, and forms an inner layer membrane with hydrophobic anti-adhesion properties through electrospinning; uses polyvinyl alcohol as a material, and forms an outer layer membrane with hydrophilic cell scaffold layer properties through electrospinning; at the same time, a transition layer is formed between the two by using a co-directional electrospinning blending process of hydrophobic polydioxanone and hydrophilic polyvinyl alcohol to achieve a stable connection between the inner layer membrane and the outer layer, so as to achieve a multi-layer degradable and absorbable electrospun artificial dura mater with good bio-tissue compatibility, complete degradation and absorption with a moderate degradation rate, no immune rejection, and mechanical strength, thickness and flexibility comparable to those of human dura mater, the inner layer and the outer layer are reliably connected, brain adhesion can be effectively prevented, and it is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the inner layer of the artificial dura mater prepared in Example 1 of the present invention;

[0033] Figure 2 This is a SEM image of the middle and outer layers of the artificial dura mater prepared in Example 1 of the present invention;

[0034] Figure 3 This is a cross-sectional SEM image of the transition layer membrane in the artificial dura mater prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.

[0036] Example 1

[0037] A multi-layered, degradable and absorbable electrospun dura mater is prepared by the following method:

[0038] S1. Preparation of inner layer film material: At room temperature, the viscosity average molecular weight of 8.4×10 4 The polydioxanone was dissolved in hexafluoroisopropanol, stirred for 5 hours to fully dissolve the polydioxanone, and allowed to stand for 2 hours to prepare an inner membrane spinning solution with a solid content of 14 wt%;

[0039] S2. Preparation of outer layer membrane material: 5 The polyvinyl alcohol is dissolved in deionized water, stirred at 95°C for 5 hours, cooled to room temperature, and an outer membrane spinning solution with a solid content of 6wt% is prepared, and the solution is allowed to stand for degassing for 2 hours; wherein the polyvinyl alcohol is PVA-117 produced by Shanghai Mairui Chemical Technology Co., Ltd., and the following embodiments are the same;

[0040] S3, preparation of transition layer membrane material: prepare the inner layer membrane spinning solution prepared in step S1 and the outer layer membrane spinning solution prepared in step S2 in a weight ratio of 8:2 of polydioxanone to polyvinyl alcohol as transition layer membrane spinning solution; in this step, the electrospinning equipment comprises two independent spinning solution supply systems, which are respectively used to store and transport polydioxanone solution and polyvinyl alcohol solution; during the spinning process, the two spinning solutions are respectively transported to the spinning needles through precise control, so that the two spinning solutions are ejected in the same direction from two needles arranged side by side, and the composite fiber is obtained after the solvent evaporates rapidly; the following preparation examples are the same;

[0041] S4. Preparation of dura mater:

[0042] The inner layer membrane spinning solution prepared in step S1 is used for electrospinning to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are set as follows: pump propulsion rate 0.1 mL / h, voltage 12 kV, receiving distance 10 cm, spinning time 3 h;

[0043] The transition layer membrane spinning solution prepared in step S3 is used to perform electrospinning on the basis of the inner layer membrane to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are set as follows: pump propulsion rate 0.2 mL / h, voltage 12 kV, receiving distance 10 cm, spinning time 3 h;

[0044] The outer layer membrane spinning solution prepared in step S2 is used to perform electrospinning on the basis of the transition layer membrane to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are set as follows: pump propulsion rate 0.3 mL / h, voltage 10 kV, receiving distance 15 cm, spinning time 3 h;

[0045] S5. The multilayer electrospinning membrane obtained in step S4 is first rinsed with distilled water for three times, and then dried at 45°C for 2 hours. After sterilization, it is vacuum-sealed and stored in a low temperature environment of -20°C.

[0046] Example 2

[0047] A multi-layered, degradable and absorbable electrospun dura mater is prepared by the following method:

[0048] S1. Preparation of inner layer film material: At room temperature, the viscosity average molecular weight of 8.4×10 4 Dissolve polydioxanone in hexafluoroisopropanol, stir for 5 hours to fully dissolve the polydioxanone, let stand for 2 hours, and prepare an inner membrane spinning solution with a solid content of 21wt%;

[0049] S2. Preparation of outer layer membrane material: 5 The polyvinyl alcohol was dissolved in deionized water and stirred at 95°C for 5 hours, cooled to room temperature, and an outer membrane spinning solution with a solid content of 9wt% was prepared, and the solution was allowed to stand for degassing for 2 hours;

[0050] S3, preparation of transition layer membrane material: prepare the inner layer membrane spinning solution prepared in step S1 and the outer layer membrane spinning solution prepared in step S2 in a weight ratio of polydioxanone to polyvinyl alcohol of 5:5 as transition layer membrane spinning solution;

[0051] S4. Preparation of dura mater:

[0052] The inner layer membrane spinning solution prepared in step S1 is used for electrospinning to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are set as follows: pump propulsion rate 0.3 mL / h, voltage 16 kV, receiving distance 13 cm, spinning time 4 h;

[0053] The transition layer membrane spinning solution prepared in step S3 is used to perform electrospinning on the basis of the inner layer membrane to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are set as follows: pump propulsion rate 0.4 mL / h, voltage 16 kV, receiving distance 13 cm, spinning time 4 h;

[0054] The outer layer membrane spinning solution prepared in step S2 is used to perform electrospinning on the basis of the transition layer membrane to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are set as follows: pump propulsion rate 0.6 mL / h, voltage 14 kV, receiving distance 17 cm, spinning time 4 h;

[0055] S5. The multilayer electrospinning membrane obtained in step S4 is first rinsed with distilled water for 4 times, and then dried at 40°C for 4 hours. After sterilization, it is vacuum-sealed and stored in a low temperature environment of -10°C.

[0056] Example 3

[0057] A multi-layered, degradable and absorbable electrospun dura mater is prepared by the following method:

[0058] S1. Preparation of inner layer film material: At room temperature, the viscosity average molecular weight of 8.4×10 4 Dissolve polydioxanone in hexafluoroisopropanol, stir for 5 hours to fully dissolve the polydioxanone, let stand for 2 hours, and prepare an inner membrane spinning solution with a solid content of 28wt%;

[0059] S2. Preparation of outer layer membrane material: 5 The polyvinyl alcohol was dissolved in deionized water and stirred at 95°C for 5 hours, cooled to room temperature, and an outer membrane spinning solution with a solid content of 12 wt% was prepared, and the solution was allowed to stand for degassing for 2 hours;

[0060] S3, preparation of transition layer membrane material: preparing the inner layer membrane spinning solution prepared in step S1 and the outer layer membrane spinning solution prepared in step S2 in a weight ratio of polydioxanone to polyvinyl alcohol of 2:8 as transition layer membrane spinning solution;

[0061] S4. Preparation of dura mater:

[0062] The inner layer membrane spinning solution prepared in step S1 is used for electrospinning to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are set as follows: pump propulsion rate 0.5 mL / h, voltage 20 kv, receiving distance 15 cm, spinning time 5 h;

[0063] The transition layer membrane spinning solution prepared in step S3 is used to perform electrospinning on the basis of the inner layer membrane to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are set as follows: pump propulsion rate 0.7 mL / h, voltage 20 kV, receiving distance 15 cm, spinning time 5 h;

[0064] The outer layer membrane spinning solution prepared in step S2 is used to perform electrospinning on the basis of the transition layer membrane to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are set as follows: pump propulsion rate 0.9 mL / h, voltage 18 kV, receiving distance 20 cm, spinning time 5 h;

[0065] S5. The multilayer electrospinning membrane obtained in step S4 is first rinsed with distilled water for 5 times, and then dried at 55°C for 3 hours. After sterilization, it is vacuum-sealed and stored in a low temperature environment of -30°C.

[0066] Example 4

[0067] A multi-layered, degradable and absorbable electrospun dura mater is prepared by the following method:

[0068] S1. Preparation of inner layer film material: At room temperature, a 5.0×10 4 Dissolve polydioxanone in hexafluoroisopropanol, stir for 6 hours to fully dissolve the polydioxanone, let stand for 3 hours, and prepare an inner membrane spinning solution with a solid content of 16 wt%;

[0069] S2. Preparation of outer layer membrane material: 5 The polyvinyl alcohol was dissolved in deionized water and stirred at 90°C for 6 hours, cooled to room temperature, and an outer membrane spinning solution with a solid content of 8 wt% was prepared, and the solution was allowed to stand for degassing for 2 hours;

[0070] S3, preparation of transition layer membrane material: prepare the inner layer membrane spinning solution prepared in step S1 and the outer layer membrane spinning solution prepared in step S2 in a weight ratio of polydioxanone to polyvinyl alcohol of 6:4 as transition layer membrane spinning solution;

[0071] S4. Preparation of dura mater:

[0072] The inner layer membrane spinning solution prepared in step S1 is used for electrospinning to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are set as follows: pump propulsion rate 0.2 mL / h, voltage 14 kV, receiving distance 12 cm, spinning time 4 h;

[0073] The transition layer membrane spinning solution prepared in step S3 is used to perform electrospinning on the basis of the inner layer membrane to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are set as follows: pump propulsion rate 0.3 mL / h, voltage 15 kv, receiving distance 11 cm, spinning time 4 h;

[0074] The outer layer membrane spinning solution prepared in step S2 is used to perform electrospinning on the basis of the transition layer membrane to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are set as follows: pump propulsion rate 0.4 mL / h, voltage 12 kV, receiving distance 18 cm, spinning time 4 h;

[0075] S5. The multilayer electrospinning membrane obtained in step S4 is first rinsed with distilled water for three times, and then dried at 45°C for 2 hours. After sterilization, it is vacuum-sealed and stored in a low temperature environment of -20°C.

[0076] Example 5

[0077] A multi-layered, degradable and absorbable electrospun dura mater is prepared by the following method:

[0078] S1. Preparation of inner layer film material: At room temperature, a 1.5×10 5Dissolve polydioxanone in hexafluoroisopropanol, stir for 4 hours to fully dissolve the polydioxanone, let stand for 1.5 hours, and prepare an inner membrane spinning solution with a solid content of 25wt%;

[0079] S2. Preparation of outer layer membrane material: 5 The polyvinyl alcohol was dissolved in deionized water and stirred at 100°C for 4 hours, cooled to room temperature, and an outer membrane spinning solution with a solid content of 10 wt% was prepared, and the solution was allowed to stand for degassing for 1.5 hours;

[0080] S3, preparation of transition layer membrane material: prepare the inner layer membrane spinning solution prepared in step S1 and the outer layer membrane spinning solution prepared in step S2 in a weight ratio of polydioxanone to polyvinyl alcohol of 3:7 as transition layer membrane spinning solution;

[0081] S4. Preparation of dura mater:

[0082] The inner layer membrane spinning solution prepared in step S1 is used for electrospinning to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are set as follows: pump propulsion rate 0.4 mL / h, voltage 18 kv, receiving distance 14 cm, spinning time 3.5 h;

[0083] The transition layer membrane spinning solution prepared in step S3 is used to perform electrospinning on the basis of the inner layer membrane to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are set as follows: pump propulsion rate 0.5 mL / h, voltage 17 kv, receiving distance 13 cm, spinning time 3.5 h;

[0084] The outer layer membrane spinning solution prepared in step S2 is used to perform electrospinning on the basis of the transition layer membrane to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are set as follows: pump propulsion rate 0.7 mL / h, voltage 16 kV, receiving distance 16 cm, spinning time 3.5 h;

[0085] S5. The multilayer electrospinning membrane obtained in step S4 is first rinsed with distilled water for three times, and then dried at 45°C for 2 hours. After sterilization, it is vacuum-sealed and stored in a low temperature environment of -20°C.

[0086] Example 6

[0087] A multi-layered, degradable and absorbable electrospun dura mater is prepared by the following method:

[0088] S1. Preparation of inner layer film material: At room temperature, the viscosity average molecular weight of 2.1×10 5 The polydioxanone was dissolved in hexafluoroisopropanol, stirred for 7 hours to fully dissolve the polydioxanone, and allowed to stand for 3.5 hours to prepare an inner membrane spinning solution with a solid content of 20 wt%;

[0089] S2. Preparation of outer layer membrane material: 5 The polyvinyl alcohol was dissolved in deionized water and stirred at 98°C for 6 hours, cooled to room temperature, and an outer membrane spinning solution with a solid content of 8 wt% was prepared, and the solution was allowed to stand for degassing for 2.5 hours;

[0090] S3, preparation of transition layer membrane material: preparing the inner layer membrane spinning solution prepared in step S1 and the outer layer membrane spinning solution prepared in step S2 in a weight ratio of polydioxanone to polyvinyl alcohol of 4:6 as transition layer membrane spinning solution;

[0091] S4. Preparation of dura mater:

[0092] The inner layer membrane spinning solution prepared in step S1 is used for electrospinning to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are set as follows: pump propulsion rate 0.3 mL / h, voltage 17 kv, receiving distance 13 cm, spinning time 4 h;

[0093] The transition layer membrane spinning solution prepared in step S3 is used to perform electrospinning on the basis of the inner layer membrane to form a transition layer membrane; the electrospinning parameters of the transition layer membrane are set as follows: pump propulsion rate 0.45 mL / h, voltage 16 kv, receiving distance 12 cm, spinning time 4 h;

[0094] The outer layer membrane spinning solution prepared in step S2 is used to perform electrospinning on the basis of the transition layer membrane to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are set as follows: pump propulsion rate 0.6 mL / h, voltage 15 kv, receiving distance 17 cm, spinning time 4 h;

[0095] S5. The multilayer electrospinning membrane obtained in step S4 is first rinsed with distilled water for three times, and then dried at 45°C for 2 hours. After sterilization, it is vacuum-sealed and stored in a low temperature environment of -20°C.

[0096] Comparative Example 1

[0097] A multi-layered degradable and absorbable electrospun dura mater, which is different from Example 4 in that: polydioxanone with a viscosity average molecular weight of 3.0×10 4 of polydioxanone.

[0098] Comparative Example 2

[0099] A multi-layered, degradable and absorbable electrospun dura mater, which is different from Example 4 in that the electrospinning parameters of the inner layer membrane are set as: pump propulsion rate 0.6 mL / h, voltage 28 kV, receiving distance 28 cm, and spinning time 4 h.

[0100] Comparative Example 3

[0101] A multi-layered, degradable and absorbable electrospun dura mater, which is different from Example 4 in that the electrospinning parameters of the outer layer are set as: pump propulsion rate 1.2 mL / h, voltage 28 kV, receiving distance 28 cm, and spinning time 4 h.

[0102] Comparative Example 4

[0103] A multi-layered, degradable and absorbable electrospun dura mater, which is different from Example 6 in that: the viscosity-average molecular weight of polydioxanone is 2.5×10 5

[0104] Comparative Example 5

[0105] A multi-layered degradable and absorbable electrospun dura mater, which is different from Example 4 in that: the polyethylene glycol has a weight average molecular weight of 8.0×10 4 of polyethylene glycol.

[0106] Comparative Example 6

[0107] A multi-layered degradable and absorbable electrospun dura mater, which is different from Example 5 in that: the polyethylene glycol has a weight average molecular weight of 2.5×10 5 of polyethylene glycol.

[0108] Comparative Example 7

[0109] A multi-layer degradable and absorbable electrospun dura mater, which is different from Example 4 in that the solid content of the inner layer membrane spinning solution is 10wt%.

[0110] Comparative Example 8

[0111] A multi-layered, degradable and absorbable electrospun dura mater, which is different from Example 4 in that the solid content of the inner layer membrane spinning solution is 35wt%.

[0112] Comparative Example 9

[0113] A multi-layer degradable and absorbable electrospun dura mater, which is different from Example 1 in that the solid content of the outer membrane spinning solution is 4wt%.

[0114] Comparative Example 10

[0115] A multi-layer degradable and absorbable electrospun dura mater, which is different from Example 1 in that the solid content of the outer membrane spinning solution is 15wt%.

[0116] Comparative Example 11

[0117] A multi-layered, degradable and absorbable electrospun dura mater, which is different from Example 1 in that: in step S3, the weight ratio of polydioxanone to polyvinyl alcohol in the transition layer membrane spinning solution is set to 9:1.

[0118] Comparative Example 12

[0119] A multi-layered, degradable and absorbable electrospun dura mater, which is different from Example 1 in that: in step S3, the weight ratio of polydioxanone to polyvinyl alcohol in the transition layer membrane spinning solution is set to 1:9.

[0120] Comparative Example 13

[0121] A multi-layered degradable and absorbable electrospun dura mater, which is different from Example 1 in that: the viscosity-average molecular weight is 8.4×10 4 The polydioxanone was replaced by a polydioxanone having a viscosity average molecular weight of 8.0×10 4 of polylactic acid.

[0122] Comparative Example 14

[0123] A multi-layer degradable and absorbable electrospun dura mater, which is different from Example 1 in that: a weight-average molecular weight of 1.45×10 5 The polyvinyl alcohol was replaced by a polyvinyl alcohol having a weight average molecular weight of 1.5×10 5 of polyethylene glycol.

[0124] Performance Test:

[0125] (I) Microstructure characteristics:

[0126] SEM was used to obtain microstructure images of different membrane layers of the artificial dura mater prepared in Examples 1 to 6 to estimate the fiber diameter and pore size in each membrane layer of the artificial dura mater in each example. The estimation results are shown in Table 1 below.

[0127] Table 1:

[0128]

[0129] From the test results in Table 1, it can be seen that the fiber diameter of the inner layer membrane of the artificial dura mater prepared in Examples 1 to 6 of the present invention is about 0.05 μm to 0.8 μm, and the pore size is about 0.2 μm to 2 μm; the fiber diameter of the outer layer membrane is about 0.5 μm to 2.2 μm, and the pore size is about 20 μm to 38 μm; and the fiber diameter of the intermediate transition layer membrane is about 0.3 μm to 2.07 μm, and the pore size is about 3 μm to 15 μm;

[0130] Based on the fact that the diameter of fibroblasts is between 20 μm and 30 μm, in the artificial dura mater in the above embodiment of the present invention, the pore size of the outer membrane is approximately in the range of 20 μm to 38 μm, which is larger than the diameter of fibroblasts, so that the outer membrane is conducive to inducing the migration, adhesion, proliferation, growth and differentiation of fibroblasts; and the pore size of the inner membrane is approximately 0.2 μm to 2 μm, which meets the requirement of being 1 to 2 orders of magnitude smaller than that of fibroblasts, and can effectively prevent cells from entering and prevent brain adhesion.

[0131] The middle transition layer is prepared by the same-direction electrospinning blending process of the hydrophobic material for the inner membrane and the hydrophilic material for the outer membrane. Therefore, its pore size range is between the pore sizes of the inner membrane and the outer membrane, and has no effect on the functions of the two. It mainly plays the role of enhancing the bonding strength between the outer layer and the inner layer.

[0132] like Figure 1 The figure shows the SEM image of the hydrophobic inner layer polydioxanone fiber membrane of the artificial dura mater prepared in Example 1. As can be seen from the figure, the fibers are randomly distributed, the thickness is relatively uniform, and the diameter is roughly between 0.09 μm and 0.8 μm. There are certain pores between the fibers, and the pores are small and uniform, with a pore size of about 0.2 μm to 1.5 μm, which can effectively prevent cells from entering and effectively prevent brain adhesion.

[0133] like Figure 2 The figure shows the SEM image of the hydrophilic outer layer polyvinyl alcohol fiber membrane of the artificial dura mater prepared in Example 1. As can be seen from the figure, the fibers are relatively loosely arranged, with a diameter in the range of 0.62 μm to 1.98 μm, and have a large number of larger pores, which are interconnected and have a pore diameter of about 20 μm to 35 μm, which meets the design requirements of the outer layer being conducive to the migration, adhesion, proliferation, growth and differentiation of fibroblasts, and can provide sufficient space for cell attachment and growth.

[0134] like Figure 3 The cross-sectional SEM image of the blended transition layer fiber membrane of polydioxanone and polyvinyl alcohol of the artificial dura mater prepared in Example 1 is shown. It can be seen from the figure that the fibers of the two materials in the intermediate transition layer membrane are tightly combined to form a relatively stable and tight composite structure; wherein, the fiber diameter in the transition layer membrane is between 0.4 μm and 2.07 μm, and the pore size is about 5 μm to 12 μm, which can not only ensure a certain barrier performance, but also achieve good stress transmission, effectively strengthen the bonding strength of the inner layer and the outer layer, ensure that the three-layer structure is not easy to peel off when subjected to external forces such as stretching, and ensure the stability of the overall structure of the artificial dura mater.

[0135] SEM was used to obtain cross-sectional microstructure images of different layers of the artificial dura mater prepared in Examples 1 to 6 to estimate the thickness of different layers of the artificial dura mater in each example. The estimated results are shown in Table 2 below.

[0136] Table 2:

[0137]

[0138] It can be seen from the test results in Table 2 that the thickness of the artificial dura mater prepared in Examples 1 to 6 ranges from 0.16 mm to 0.22 mm, which is consistent with the thickness of the human dura mater between 0.1 mm and 0.5 mm; specifically, the thickness of the inner layer membrane is 80±10 μm, the thickness of the transition layer membrane is 80±10 μm, and the thickness of the outer layer membrane is 30±10 μm, which are also respectively consistent with the thickness of the inner layer membrane and the outer mold layer in the human dura mater, which makes the artificial dura mater of the present invention easy to operate during the implantation process in terms of surgical operation, such as convenience and fit during suturing. Avoid problems such as suturing difficulties, increased operation time and risks, and affected surgical results caused by large differences in thickness; secondly, from the perspective of mechanical properties, artificial meninges with a thickness equivalent to that of human meninges can better withstand intracranial physiological pressure and external forces generated by brain movement, maintain structural stability, prevent rupture or deformation, and effectively protect brain tissue; thirdly, from the perspective of the tissue repair process, appropriate thickness helps cell migration, proliferation and differentiation, promotes the regeneration and repair of meningeal tissue, provides cells with a suitable growth environment, reduces adverse reactions caused by inappropriate thickness, improves clinical treatment effects, and ensures patient health.

[0139] (II) Mechanical properties test:

[0140] The tensile strength of the multi-layered degradable and absorbable electrospun dura mater prepared in Examples 1 to 5 was tested using a universal material testing machine at a tensile rate of 10 mm / min.

[0141] The specific test results are shown in Table 3 below.

[0142] Table 3:

[0143] Test Case Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Tensile Strength 8.5MPa 10.2MPa 11.9MPa 7.8MPa 10.5MPa 9.2MPa

[0144] From the test results in Table 3, it can be seen that the tensile strength of the multi-layer degradable and absorbable electrospun dura mater prepared in Examples 1 to 6 is 7.8 MPa to 11.9 MPa, which is comparable to the general range of 5 MPa to 15 MPa of the human dura mater, indicating that the requirements for the mechanical properties of the material can be met during surgical repair, and that it can withstand a certain external force without rupture or deformation after suturing and implantation.

[0145] In addition, after the above-mentioned tensile strength test, it was observed that the artificial dura mater prepared in each embodiment had no obvious structural damage such as delamination, cracking, wrinkling or fiber breakage, which indicates that the three-layer structure of the artificial dura mater is not easy to peel off when subjected to external forces such as tension, confirming that the inner layer and the outer layer of the artificial dura mater of the present invention are connected by the transition layer, thereby achieving the stability of the overall membrane structure of the artificial dura mater.

[0146] (III) Degradation performance test:

[0147] In the degradation experiment in a simulated human physiological environment (37°C, pH=7.4 phosphate buffer solution), the degradation experiment time was set to 1 month, and the mass residual rate of the tested membrane was obtained after the experiment; the specific test results are shown in Table 4 below.

[0148] Table 4:

[0149] Test Case Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Quality Residual Rate 88% 90% 92% 85% 89% 87%

[0150] From the test results in Table 4, it can be seen that the mass residual rate of the multi-layer degradable and absorbable electrospun dura mater prepared in Examples 1 to 6 after the degradation experiment is 85% to 92%. It can be estimated that the artificial dura mater prepared in each example can eventually be basically completely degraded after 6 to 8 months, which matches the physiological repair cycle of the human dura mater after injury. It can not only maintain structural integrity for a certain period of time to support the meningeal repair process, but also gradually degrade over time. It will not cause incomplete repair due to too fast degradation, nor will it cause complications due to too slow degradation and long-term retention in the body, which reflects its advantage of moderate degradation speed.

[0151] In addition, from the perspective of the composition of the artificial dura mater of the present invention, the presence of the transition layer can regulate the degradation performance of the entire membrane, so that during the degradation process of the artificial dura mater in the body, from the outer membrane to the inner membrane, the transition layer is added to avoid sudden degradation acceleration, and the degradation rate is gradually accelerated through the transition layer membrane, ensuring that the degradation process in the human body is more stable and avoiding structural failure problems caused by excessively fast or slow local degradation.

[0152] (IV) Cell affinity performance test:

[0153] The number is 5×10 4 Fibroblasts were inoculated on the surface of the artificial dura mater sample. After culturing for 72 hours, the number of fibroblasts adhered to each square millimeter of the artificial dura mater surface was determined by fluorescence staining. The specific test results are shown in Table 5 below.

[0154] Table 5:

[0155] Test Case Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 quantity 240±20 270±25 300±30 200±20 250±25 230±22

[0156] From the test results in Table 5, it can be seen that after 72 hours of culture, the number of fibroblasts adhering to the surface of the artificial dura mater prepared by the multi-layer degradable and absorbable electrospun dura mater of Examples 1 to 6 is more than 200±20 per square millimeter, which is doubled compared with the ordinary tissue culture plate (about 100±15 per square millimeter), indicating that the artificial dura mater has a strong initial adsorption capacity for fibroblasts; in addition, the fibroblasts after culture have normal morphology, indicating that the material has good cell affinity and stable cell adsorption capacity, and can provide a suitable attachment environment for cells, which is conducive to the migration, adhesion, proliferation and growth differentiation of cells, and promotes the repair of meningeal tissue.

[0157] In the process of preparing the artificial dura mater of the present invention, various process parameters related to the performance indicators of the artificial dura mater are explored and experimented to obtain the optimal process parameters for preparing the artificial dura mater; in this specific embodiment, some of the exploration experiments are selected as comparative examples for illustration, specifically referring to Comparative Examples 1 to 14.

[0158] The tensile strength of the artificial dura mater prepared in Example 4 is 7.8 MPa; compared with Example 4:

[0159] The tensile strength of the artificial dura mater prepared in Comparative Example 1 was tested to be 4 MPa. It can be seen that the tensile strength of the artificial dura mater prepared in Comparative Example 1 was greatly reduced due to the low viscosity-average molecular weight of polydioxanone. This is specifically because the molecular weight of polydioxanone is low, so the molecular chain is short, and it is difficult to form a tightly entangled fiber structure during the spinning process, resulting in a loose fiber structure of the inner layer membrane and weakened interaction between fibers. In turn, the artificial dura mater formed by the inner layer membrane with a loose fiber structure has changes in mechanical properties and cannot meet clinical use requirements.

[0160] The tensile strength of the artificial dura mater prepared in Comparative Example 2 was tested to be 5.5 MPa. It can be seen that compared with Example 4, the tensile strength of the artificial dura mater prepared in Comparative Example 2 was greatly reduced due to the change in the electrospinning parameter setting of the inner layer membrane; this is specifically due to the unreasonable electrospinning parameter setting of the inner layer membrane, including excessive propulsion rate, excessive voltage and receiving distance, resulting in uneven solution ejection amount and electric field force, and manifested as uneven fiber diameter and thickening of some fibers; the inner layer membrane prepared in Comparative Example 2 was estimated by its SEM image, and the fibers The diameter is 0.2 μm to 1 μm, which is 0.05 μm to 0.5 μm compared with the fiber diameter of the inner layer membrane prepared in Example 4. There is obviously a problem of poor uniformity of fiber diameter and thickening of some fibers; in addition, the inner layer membrane prepared in Comparative Example 2 also has the problem of disordered fiber arrangement from the SEM image. The above two reasons ultimately lead to changes in the mechanical properties of the artificial dura mater formed by the above inner layer membrane, which cannot meet the clinical use requirements, and also illustrate the necessity of matching the electrospinning parameters with the spinning solution materials;

[0161] The tensile strength of the artificial dura mater prepared in Comparative Example 3 was tested to be 6 MPa. It can be seen that compared with Example 4, the tensile strength of the artificial dura mater prepared in Comparative Example 3 was reduced due to the change in the electrospinning parameter setting of the outer layer membrane; this was specifically due to the unreasonable electrospinning parameter setting of the outer layer membrane, including excessive propulsion rate, excessive voltage and receiving distance, resulting in uneven solution ejection amount and electric field force, and manifested as uneven fiber diameter and thickening of some fibers; through observation of the outer layer membrane, it can be seen that the fibers are poorly formed, a large number of fiber bundles of uneven thickness appear, and are not tightly combined with the inner layer and the transition layer, which ultimately leads to changes in the mechanical properties of the artificial dura mater formed by the above-mentioned outer layer membrane, which cannot meet the clinical use requirements; this Comparative Example 3 is the same as Comparative Example 2, which once again proves the negative impact of unreasonable spinning parameters on material properties, especially in terms of synergy with other layers.

[0162] The tensile strength of the artificial dura mater prepared in Comparative Example 7 was tested to be 6.5 MPa. It can be seen that, compared with Example 4, the tensile strength of the artificial dura mater prepared in Comparative Example 7 was reduced due to the low solid content of the inner membrane spinning solution; this is specifically because in the electrospinning process, the low solid content of the spinning solution will cause the fiber diameter to become thinner (0.1 μm to 0.4 μm) and the fiber structure to be loosely stacked, thereby causing the mechanical properties to decrease; while Example 4 uses a spinning solution with a higher and appropriate solid content to increase the viscosity of the spinning solution to adapt to the electrospinning parameters, so that the fibers are stretched and stacked more tightly in the electric field, forming a denser fiber structure, and effectively enhancing the tensile strength of the membrane;

[0163] The tensile strength of the artificial dura mater prepared in Comparative Example 8 was tested to be 5 MPa. It can be seen that, compared with Example 4, the tensile strength of the artificial dura mater prepared in Comparative Example 8 was greatly reduced due to the excessively high solid content of the inner membrane spinning solution; this is specifically because the excessively high inner membrane spinning solution leads to excessive viscosity of the spinning solution, which causes poor fluidity, easy clogging of the needle, and unstable jet in the electric field during the electrospinning process, making it difficult to carry out the spinning process stably, and the defects of the formed fiber structure also increase, and the mechanical properties deteriorate, which cannot meet the clinical use requirements.

[0164] The tensile strength of the artificial dura mater prepared in Example 5 is 10.5 MPa; compared with Example 5:

[0165] The tensile strength of the artificial dura mater prepared in Comparative Example 4 was tested to be 9 MPa. It can be seen that, compared with Example 5, the tensile strength of the artificial dura mater prepared in Comparative Example 4 was reduced due to the excessively high viscosity-average molecular weight of polydioxanone; this is specifically due to the incomplete dissolution of polydioxanone with an excessively high molecular weight when preparing the inner membrane spinning solution, the easy generation of bubbles in the solution, and the poor stability of the solution, resulting in fiber defects and structural unevenness during the electrospinning process, which in turn affected the mechanical properties, resulting in the artificial dura mater formed by the above-mentioned inner membrane failing to meet clinical use requirements.

[0166] The tensile strength of the artificial dura mater prepared in Comparative Example 5 was tested to be 4.5 MPa. It can be seen that compared with Example 5, the tensile strength of the artificial dura mater prepared in Comparative Example 5 was greatly reduced due to the low weight average molecular weight of polyethylene glycol. This is specifically because the molecular chain of polyethylene glycol with too low molecular weight is relatively short, and it is difficult to form effective chemical bonds and physical entanglements when combining with the inner layer and the transition layer, which affects the combination effect with the inner layer and the transition layer, and then the mechanical properties change, and cannot meet the clinical use requirements; in addition, in the cell affinity test of the artificial dura mater formed by the outer layer membrane, after 72 hours of culture, the number of fibroblasts attached to the surface of the artificial dura mater is only about 150±15 per square millimeter, indicating that the low weight average molecular weight of polyethylene glycol will lead to the poor hydrophilicity of the outer layer membrane and the ability to form a hydration layer, which is not conducive to the formation of a good cell attachment microenvironment.

[0167] The tensile strength of the artificial dura mater prepared in Comparative Example 6 was tested to be 8.5 MPa. It can be seen that, compared with Example 5, the tensile strength of the artificial dura mater prepared in Comparative Example 6 was greatly reduced due to the excessively high weight average molecular weight of polyethylene glycol; this is specifically due to the incomplete dissolution of the polyethylene glycol with an excessively high molecular weight when preparing the outer membrane spinning solution, and the excessive viscosity of the spinning solution, which resulted in the problem of difficult transportation during the electrospinning process, affecting the spinning continuity and fiber uniformity, resulting in a decrease in the quality of the outer membrane, causing the mechanical properties of the artificial dura mater formed by the above outer membrane to deteriorate and fail to meet clinical use requirements.

[0168] The tensile strength of the artificial dura mater prepared in Example 1 is 8.5 MPa; compared with Example 1:

[0169] The tensile strength of the artificial dura mater prepared in Comparative Example 9 was tested to be 7 MPa. It can be seen that compared with Example 1, the tensile strength of the artificial dura mater prepared in Comparative Example 9 is reduced due to the low solid content of the outer membrane spinning solution; this is specifically because during the electrospinning process, the low solid content of the spinning solution will cause the fiber diameter to become thinner (0.3 μm to 0.8 μm) and the fiber structure to be loosely stacked, thereby causing a decrease in mechanical properties; this is consistent with the comparison conclusions of the above-mentioned Example 4 and Comparative Example 7.

[0170] The tensile strength of the artificial dura mater prepared in Comparative Example 10 was tested to be 6 MPa. It can be seen that compared with Example 1, the tensile strength of the artificial dura mater prepared in Comparative Example 10 was greatly reduced due to the excessively high solid content of the outer membrane spinning solution; this is specifically because the excessively high outer membrane spinning solution leads to excessive viscosity of the spinning solution, which causes poor fluidity, easy clogging of the needle, and unstable jet in the electric field during the electrospinning process, making it difficult to carry out the spinning process stably, and the defects of the formed fiber structure also increase accordingly, ultimately resulting in the deterioration of the mechanical properties of the artificial dura mater, which cannot meet the clinical use requirements; this is consistent with the comparison conclusion of the above-mentioned Example 4 and Comparative Example 8.

[0171] The tensile strength of the artificial dura mater prepared in Comparative Example 11 was tested to be 6 MPa. It can be seen that, compared with Example 1, the tensile strength of the artificial dura mater prepared in Comparative Example 11 was reduced due to the excessively high proportion of polydioxanone in the transition layer membrane; this is specifically because the proportion of polyvinyl alcohol in the transition layer membrane is too low, resulting in a weakening of the similar compatibility principle between it and the outer layer membrane, which is manifested as a deterioration in the bonding force between the transition layer membrane and the outer layer membrane, and uneven stress transmission, which ultimately leads to a deterioration in the mechanical properties of the artificial dura mater, and cannot meet the clinical use requirements;

[0172] The tensile strength of the artificial dura mater prepared in Comparative Example 12 was tested to be 5.5 MPa. It can be seen that, compared with Example 1, the tensile strength of the artificial dura mater prepared in Comparative Example 12 was greatly reduced due to the excessively high proportion of polyvinyl alcohol in the transition layer membrane; this is specifically because the proportion of polydioxanone in the transition layer membrane is too low, resulting in a weakening of the similar compatibility principle between it and the inner layer membrane, which is manifested as a deterioration in the bonding force between the transition layer membrane and the inner layer membrane, uneven stress transmission, and ultimately resulting in a deterioration in the mechanical properties of the artificial dura mater, which cannot meet the clinical use requirements;

[0173] The tensile strength of the artificial dura mater prepared in Comparative Example 13 was tested to be 5 MPa. It can be seen that, compared with Example 1, the tensile strength of the artificial dura mater prepared in Comparative Example 13 was greatly reduced due to the change in the inner layer membrane material. This is specifically because although the polylactic acid used to prepare the inner layer membrane in Comparative Example 13 has a molecular weight similar to that of the polydioxanone used to prepare the inner layer membrane in Example 1, the two materials have differences in chemical structure, which makes the fiber structure of the inner layer membrane formed by polylactic acid loose, thereby reducing the tensile strength. In addition, in the degradation experiment, the comparative example The mass residual rate after the degradation experiment is 95%, and the degradation cycle is too long. In addition, polylactic acid will produce acidic substances during the degradation process, which will affect the pH of the surrounding tissue microenvironment and easily cause inflammation. In the cell affinity test of the artificial dura mater prepared in this comparative example, after 72 hours of culture, the number of fibroblasts adhering to the surface of the artificial dura mater per square millimeter is only about 120±10. It can be seen that the change of the inner membrane material causes the artificial dura mater to be inferior to the artificial dura mater prepared in Example 1 in terms of mechanical properties, degradation properties and cell affinity, and cannot meet the clinical use requirements.

[0174] The tensile strength of the artificial dura mater prepared in Comparative Example 14 was tested to be 6 MPa. It can be seen that, compared with Example 1, the tensile strength of the artificial dura mater prepared in Comparative Example 14 was greatly reduced due to the change in the outer membrane material. This is specifically because although the polyethylene glycol used to prepare the outer membrane in Comparative Example 14 has a molecular weight similar to that of the polyvinyl alcohol used to prepare the outer membrane in Example 1, the two materials have differences in chemical structure, and the outer membrane formed by polyethylene glycol has a poor binding effect with the transition layer membrane, resulting in a decrease in the tensile strength of the artificial dura mater. In addition, in the cell affinity test, after 72 hours of culture, the number of fibroblasts attached to each square millimeter of the artificial dura mater surface is only about 130±12. It can be seen that the change in the outer membrane material causes the artificial dura mater to be inferior to the artificial dura mater prepared in Example 1 in both mechanical properties and cell affinity.

[0175] Parts of the present invention that are not disclosed in detail belong to the common knowledge in the art. Although the above describes the illustrative specific embodiments of the present invention to facilitate the understanding of the present invention by those skilled in the art, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. A multi-layered, degradable and absorbable electrospun artificial dura mater, characterized in that: The dura mater is composed of an inner membrane, a transitional membrane, and an outer membrane arranged in sequence; The formed hydrophobic anti-adhesion layer has a membrane pore size ranging from 0.2 μm to 2 μm; The transition layer film is composed of a viscosity average molecular weight of 5.0×10 4 ~2.1×10 5 The polydioxanone with a viscosity average molecular weight of 1.45×10 5 ~2×10 5 The weight ratio of polyvinyl alcohol is 2:8 to 8:2, and the intermediate layer is formed by electrospinning, and the membrane pore size ranges from 2μm to 20μm; The outer layer film is made of a viscosity average molecular weight of 1.45×10 5 ~2×10 5 The hydrophilic cell scaffold layer is formed by electrospinning of polyvinyl alcohol, and its membrane pore size ranges from 20μm to 40μm.

2. The multi-layered, degradable and absorbable electrospun artificial dura mater according to claim 1, characterized in that: The thickness of the dura mater is 0.16mm~0.22mm; among them, the thickness of the inner layer is 80μm±10μm, the thickness of the transition layer is 80μm±20μm, and the thickness of the outer layer is 30μm±10μm.

3. The multi-layered, degradable and absorbable electrospun artificial dura mater according to claim 1, characterized in that: The diameter of the electrospun fibers of the inner layer membrane is 0.05 μm to 1 μm, the diameter of the electrospun fibers of the outer layer membrane is 0.5 μm to 3 μm, and the diameter of the electrospun fibers of the transition layer membrane is 0.2 μm to 3 μm.

4. A method for preparing a multi-layered, degradable and absorbable electrospun artificial dura mater according to any one of claims 1 to 3, characterized in that: The steps are: (1) electrospinning an inner layer membrane spinning solution having a solid content of polydioxanone of 14 wt% to 28 wt% to form an inner layer membrane; the electrospinning parameters of the inner layer membrane are: a pump propulsion rate of 0.1 mL / h to 0.5 mL / h, a voltage of 12 kv to 20 kv, a receiving distance of 10 cm to 15 cm, and a spinning time of 3 h to 5 h; (2) Based on the inner layer membrane, electrospinning a transition layer membrane spinning solution prepared by mixing an inner layer membrane spinning solution with a solid content of 14 wt% to 28 wt% and an outer layer membrane spinning solution with a solid content of 6 wt% to 12 wt% is performed to form a transition layer membrane spinning solution; The electrospinning parameters of the transition layer membrane are: pump propulsion rate 0.2mL / h~0.7mL / h, voltage 12kv~20kv, receiving distance 10cm~15cm, spinning time 3h~5h; (3) On the basis of the transition layer membrane, an outer layer membrane spinning solution with a solid content of polyvinyl alcohol of 6wt% to 12wt% is electrospun to form an outer layer membrane; the electrospinning parameters of the outer layer membrane are: pump propulsion rate 0.3mL / h to 0.9mL / h, voltage 10kv to 18kv, receiving distance 15cm to 20cm, and spinning time 3h to 5h.

5. The multi-layered, degradable and absorbable electrospun artificial dura mater according to claim 4, characterized in that: In step (1), the inner layer membrane spinning solution is prepared by dissolving polydioxanone in hexafluoroisopropanol, stirring for 4 hours to 7 hours to fully dissolve the polydioxanone, and preparing the inner layer membrane spinning solution.

6. The multi-layered biodegradable and absorbable electrospun artificial dura mater according to claim 4, characterized in that: In step (2), the outer layer membrane spinning solution is prepared by dissolving polyvinyl alcohol in deionized water, stirring at 90°C to 100°C for 4h to 6h, and cooling to room temperature to prepare the outer layer membrane spinning solution.

7. The multi-layered, degradable and absorbable electrospun artificial dura mater according to claim 4, characterized in that: In steps (1) to (3), after the preparation of each spinning solution is completed, it is allowed to stand and degas for 1.5 hours to 3.5 hours.

8. The multi-layered, degradable and absorbable electrospun artificial dura mater according to claim 4, characterized in that: The method further comprises the step (4): the multilayer electrospinning membrane prepared through the steps (1) to (3) is first rinsed with distilled water for 3 to 5 times, and then dried at 40°C to 55°C for 2h to 4h, and then sterilized and vacuum-sealed and stored in a low temperature environment of -10°C to -30°C.

Citation Information

Patent Citations

  • Nano artificial dura mater with multi functional-layers and preparation method thereof

    CN101507661B

  • Artificial dura mater spinalis, and preparation method and use method thereof

    CN103480042A

  • A multilayer fused electrospun artificial dura mater and its preparation method

    CN107823713B

  • A multifunctional dura mater repair material based on biomimetic design and its preparation method

    CN109260520B